(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
في العلوم الفيزيائية وفي العلوم التقنية وفي مجالات أخرى من العلوم ، تصادفنا بشكل خاص مسائل تبحث في عمليات الاهتزاز، وهذه المسائل تملك صفات نبضية أو ما يسمى بصفات دفعية، أما في الرياضيات المتقدمة فقد تسمى هذه العمليات بجملة المعادلات التفاضلية تحت التأثير النبضي، وهي عملياً استمرار لطرائق تصميم الساعات. ففي القرن التاسع عشر ومطلع القرن العشرين ومن خلال نظرية المعادلات التفاضلية سواء أكانت معادلات تفاضلية خطية أم غير خطية لم يعط للصفات النبضية أية أهمية تذكر، فإجمالاً معظم الحركات الاهتزازية أو الدورانية تخضع لتأثيرات نبضية تعاني منها المنحنيات البيانية، ولهذه المجموعات التفاضلية بالتأثير النبضي صفات مميزة سيتم معالجتها من خلال فقرات هذا البحث، وسندرس أيضا بعض مشاكل النظريات الخطية بتأثير نبضي. In physics, technical sciences and other fields of science ,we come across unique problems researching oscillator processes, and these problems possess impulsive characteristics or what is called impulsion characteristics . But in developed mathematics this process differential equations under influence of pulse, this is in the empirically continuous methods of the watches design. In the nineteenth century and the early twentieth century through the theorem of differential equations either linear differential equation or nonlinear not much attention was given to impulsive characteristics. Almost the oscillation motions or circulation has impulsive characteristics which suffer from data curves. These differential groups with impulsive influence have distinguished characteristics which are going to be examined through in this research. Moreover, some problems of the linear theorems user influence of pulse will also be looked at.